Penerapan Model Pembelajaran Mastery Learning untuk Meningkatkan Hasil Belajar Siswa Pada Mata Pelajaran Pendidikan Kewarganegaraan Kelas IV SD Negeri 0117 Sibuhuan - Sri Devy Nur Siagian; Lina Mayasari Siregar; Rizki Hamdan Saputra (Jurnal Kajian Penelitian Pendidikan dan Kebudayaan, 2023)
Based on the results of the research, it can be concluded that (1) Student learning outcomes in citizenship education subjects on understanding freedom of organization in class IV of SD Negeri 0117 Sibuhuan, Barumun District, Padang Lawas Regency before implementing the mastery learning model obtained a total of 1975 students' average score. was 63.71 and there were 23 students who scored below the KKM 75 with a percentage of 74.19% and 8 students scored above the KKM with a percentage of 25.81%. So it can be seen that learning in the pre-cycle has not been able to improve Civics learning outcomes. So the researcher tried to change the implementation of the teaching and learning process by using a learning model, namely mastery learning. (2) Improved student learning outcomes in citizenship education subjects on understanding freedom of organization in class IV of SD Negeri 0117 Sibuhuan, Barumun District, Padang Lawas Regency, after implementing the mastery learning model in cycle I, obtaining a total of 2300 marks, the average value of students was 74.19 . Of the 31 students who got a score below the KKM of 75, there were 12 students with a percentage of 38.71% and 19 students got a score above the KKM with a percentage of 61.21%, while in the second cycle they got a total of 2575 scores. The average score for students was 83. .06, of the 31 students who got a score below the KKM 75 there were 3 students with a percentage of 10.00% and there were 3 students with a percentage of 9.68% and 28 students got a score above the KKM with a percentage of 90.32%.